An assessment of the solar photovoltaic generation yield in Malaysia using satellite derived datasets - Ahmed, Tofael; Mekhilef, Saad; Shah, Rakibuzzaman; Mithulananthan, Nadarajah (Regional Energy Resources Information Center (RERIC), Asian Institute of Technology, 2019)
Precise and reliable estimation of energy yield for solar photovoltaic (PV) system is imperative for the accurate design of PV system components and power system planning studies with high penetration of renewables. A number of studies have conducted related to PV yield assessments in Europe and some parts of Asia. However, PV yield assessment for various locations in Malaysia is yet to be conducted. This work assesses the average annual PV yield (kWh/kWp/y) in Malaysia for the installed capacity in 2015. Meteorological data from Photovoltaic Geographic Information System (PVGIS) is utilized for yield evaluation. The comparative yield estimation based on PVGIS and yearlong-recorded data for installed PV system at the University of Malaya is conducted first. A little error is observed between the field measurements and the yield studies based on PVGIS data. Then, the expected average yield for the individual region in Malaysia is estimated from PVGIS. Finally, based on the obtained results the individual region in Malaysia is ranked for PV availability. This study could provide very useful information to the power utilities, PV industries, and policymakers regarding the planning of large-scale PV plant, network operation, and future PV system development in Malaysia. © 2019 Regional Energy Resources Information Center (RERIC). All rights reserved.